Genetic Diversity of Arabica Coffee (Coffea arabica L.) in Nicaragua as Estimated by Simple Sequence Repeat Markers. (4th June 2012) - Geleta, Mulatu; Herrera, Isabel; Monzón, Arnulfo; Bryngelsson, Tomas
Abstract : Coffea arabica L. (arabica coffee), the only tetraploid species in the genus Coffea, represents the majority of the world's coffee production and has a significant contribution to Nicaragua's economy. The present paper was conducted to determine the genetic diversity of arabica coffee in Nicaragua for its conservation and breeding values. Twenty-six populations that represent eight varieties in Nicaragua were investigated using simple sequence repeat (SSR) markers. A total of 24 alleles were obtained from the 12 loci investigated across 260 individual plants. The total Nei's gene diversity (H T ) and the within-population gene diversity (H S ) were 0.35 and 0.29, respectively, which is comparable with that previously reported from other countries and regions. Among the varieties, the highest diversity was recorded in the variety Catimor. Analysis of variance (AMOVA) revealed that about 87% of the total genetic variation was found within populations and the remaining 13% differentiate the populations (F S T = 0.13 ; P < 0.001 ). The variation among the varieties was also significant. The genetic variation in Nicaraguan coffee is significant enough to be used in the breeding programs, and most of this variation can be conserved through ex situ conservation of a low number of populations from each variety.